Sociability and gazing toward humans in dogs and wolves: Simple behaviors with broad implications - Bentosela, Mariana (2016)
Sociability, defined as the tendency to approach and interact with unfamiliar people, has been found to modulate some communicative responses in domestic dogs, including gaze behavior toward the human face. The objective of this study was to compare sociability and gaze behavior in pet domestic dogs and in human‐socialized captive wolves in order to identify the relative influence of domestication and learning in the development of the dog–human bond. In Experiment 1, we assessed the approach behavior and social tendencies of dogs and wolves to a familiar and an unfamiliar person. In Experiment 2, we compared the animal's duration of gaze toward a person's face in the presence of food, which the animals could see but not access. Dogs showed higher levels of interspecific sociability than wolves in all conditions, including those where attention was unavailable. In addition, dogs gazed longer at the person's face than wolves in the presence of out‐of‐reach food. The potential contributions of domestication, associative learning, and experiences during ontogeny to prosocial behavior toward humans are discussed.